Disease assessment in systemic vasculitis - Luqmani, R (2004)
The vasculitides represent a set of uncommon but chronic persistent relapsing disorders which were previously fatal without the advent of effective immunosuppressive therapy. In the absence of a cure for most forms of vasculitis, we need to use accurate tools to measure disease status in order to establish an appropriate therapeutic regimen in every case. Accurate serological markers of disease activity remain elusive. Therefore, the clinician must use the quantitative and qualitative information available from careful clinical evaluation of these patients. Effective measurement of disease activity disease damage and function are the current gold standards of evaluation of patient status. In this paper, we review the evidence for the usefulness of serological markers of disease activity and discuss the role of the Birmingham Vasculitis Activity Score, the Vasculitis Damage Index and the Short Form 36 in the comprehensive evaluation of systemic vasculitis. ©Asia Pacific League of Associations for Rheumatology.